The Impact of Courageous Leadership Practices on Enhancing Entrepreneurial Behavior in Human Resources - Mahmoud Ayed Hassan (Universitas Negeri Malang, 2026)
This study will study the effect of courageous leadership which is an independent variable affecting the entrepreneurial behavior of the human resource management which is a dependent variable to the Ministry of Labor and Social Affairs. As the subject is very important for public organizations given their role in the society, the research used a descriptive-analytical methodology. This study accessed a purposive sample of 125 respondents, that included senior, middle and executive leaders. The main research tool was 30-item questionnaire. Data analysis was done through SPSS (version 25) applying mean, standard deviation, coefficient of variation, R2, F-test, simple linear regression, relative importance and Pearson correlation test to check the hypothesis. The results showed that the dimensions of courageous leadership are collectively used by administrative leaders to better strengthen HR entrepreneurial behavior rather than through the individual dimension, indicating a high correlation and combination between each dimension of courageous leadership and promoting proactive and innovative behavior.